Conducting polymers with defined micro- or nanostructures for drug delivery. (December 2016) - Uppalapati, Dedeepya; Boyd, Ben J.; Garg, Sanjay; Travas-Sejdic, Jadranka; Svirskis, Darren
Abstract: Conducting polymers (CPs) are redox active materials with tunable electronic and physical properties. The charge of the CP backbone can be manipulated through redox processes, with accompanied movement of ions into and out of the polymer to maintain electrostatic neutrality. CPs with defined micro- or nanostructures have greatly enhanced surface areas, compared to conventionally prepared CPs. The resulting high surface area interface between polymer and liquid media facilities ion exchange and can lead to larger and more rapid responses to redox cycling. CP systems are maturing as platforms for electrically tunable drug delivery. CPs with defined micro- or nanostructures offer the ability to increase the amount of drug that can be delivered whilst enabling systems to be finely tuned to control the extent and rate of drug release. In this review, fabrication approaches to achieve CPs with micro- or nanostructure are outlined followed by a detailed review and discussion of recent advances in the application of the materials for drug delivery.